ANTIBACTERIAL EFFECTIVENESS OF RAMBAI (Sonneratia Caseolaris) LEAVES EXTRACT AGAINST STREPTOCOCCUS MUTANS - Nor Rahmatika, Aniqah; Aspriyanto, Didit; Ichrom Nahzi, Muhammad Yanuar (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: The 2018 Riskesdas data stated that dental caries prevalence in Indonesia was 88.8%. Dental caries is a multifactorial disease characterized by hard tissue damage to the enamel, dentin, and cementum of the teeth. One of the causes of caries is the presence of a microorganism called Streptococcus mutans. Rambai leaf extract (Sonneratia caseolaris) is a typical plant of South Kalimantan with content flavonoids, tripernoids, tannins, phenols, steroids that have antibacterial properties against the growth of Streptococcus mutans which can prevent caries. Purpose: To determine the difference in the effectiveness of the antibacterial extract of rambai leaves (Sonneratia caseolaris) against bacteria Streptococcus mutans in vitro. Methods: This research was a true experimental with a post-test-only design and a control group, using six treatment groups, namely 20%, 40%, 60%, 80%, positive control (povidone iodine 1%), and negative control (aquadest) respectively. Each treatment got 3 repetitions. The antibacterial test method used in this study was the liquid dilution method to determine the Minimun Inhibitory Concentration (MIC) by using Spectrophotometer and solid dilution to determine the Minimum Bactericidal Concentration (MBC) by using tools Colony Counter. Results: Based on the results and data analysis, it can be seen that the rambai leaf extract has a MIC of 20% and a MBC of 60%. Conclusion: Rambai leaf extract (Sonneratia caseolaris) can inhibit and have antibacterial activity against the growth of Streptococcus mutans. Keywords: Antibacterial, Rambai leaf extract, Streptococcus mutans